Transit of pp60v-src to the plasma membrane. - Courtneidge, S A (1982)
The protein kinase (pp60v-src) encoded by the transforming gene (v-src) of Rous sarcoma virus is synthesized on free polyribosomes and then translocated to the plasma membrane of infected cells. Neither the mechanism of the translocation nor the physiological significance of the membrane localization has been elucidated. We have explored these problems by pursuing previous observations of a complex between pp60v-src and two cellular proteins with molecular weights of 50,000 and 89,000. We found the complex located entirely in the cytoplasm, where it appears to form immediately after the synthesis of pp60v-src. While in the complex, pp60v-src has little detectable kinase activity and is phosphorylated predominantly on serine. After transfer from the complex to the plasma membrane, pp60v-src becomes phosphorylated on tyrosine as well as serine and acquires kinase activity. Under restrictive conditions, temperature-sensitive pp60v-src is produced in normal quantities, but translocation to the plasma membrane is diminished. As an apparent consequence, the cytoplasmic complex accumulates to abnormal abundance. Alternatively, temperature-sensitive pp60v-src that has been synthesized and translocated to the plasma membrane under permissive conditions appears to be released from the membrane and returns to the cytoplasmic complex when the infected cells are shifted to the restrictive temperature. We conclude that the cytoplasmic complex may be the vehicle by which pp60v-src reaches the plasma membrane. It is possible that other proteins may follow a similar route to the membrane. Binding to plasma membrane appears to be a discrete step in the biogenesis of pp60v-src and may be essential to the function of the protein.